Peer-Based Reproductive Health Promotion on Nursing Student Self-Efficacy in Kabanjahe, North Sumatra - Juli Evianna Br Purba; Rio Jenita Sipayung; Rizka Sititah Rambe (Media of Health Research, 2026)
Reproductive health self-efficacy among nursing students in semi-urban Indonesia remains inadequately addressed. In Kabanjahe, Karo Regency, North Sumatra, structured reproductive health promotion within nursing education is largely absent. This study evaluated the effectiveness of a peer-based reproductive health promotion programme on self-efficacy among nursing students in Kabanjahe. A quasi-experimental pre-test–post-test control group design was conducted with 62 nursing students (31 per group) recruited via purposive sampling. The intervention comprised six peer-led sessions of 90 minutes each over six weeks. Self-efficacy was measured using the validated Reproductive Health Self-Efficacy Scale (RHSES-25; Cronbach's α = 0.887). The intervention group demonstrated significant improvement in self-efficacy (pre: 56.84 ± 6.52; post: 67.91 ± 5.87; p < 0.001; Cohen's d = 1.82), while the control group showed no significant change (p = 0.098; d = 0.31). The between-group post-test difference was highly significant (p < 0.001; d = 1.46). Multiple regression identified group allocation (β = 0.523) and baseline self-efficacy (β = 0.312) as significant predictors (R² = 0.524). Peer-based reproductive health promotion significantly improved self-efficacy among nursing students in Kabanjahe and represents a scalable, culturally responsive model replicable across semi-urban districts in Indonesia.